2003
DOI: 10.1038/sj.ijo.0802277
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake, eating behavior, and physical activity-related determinants of high body mass index in rural communities in Wyoming, Montana, and Idaho

Abstract: OBJECTIVE:To assess the relation between body mass index (BMI) levels and various lifestyle variables related to physical activity and specific characteristics of a healthy eating pattern, using baseline cross-sectional data from the Wellness IN the Rockies project. SUBJECTS: A total of 928 males and 889 females, aged 18-99 y, recruited from six rural communities in Wyoming, Montana, and Idaho. MEASUREMENTS: Using BMI as the criterion, overweight was defined as a BMI X25 kg/m 2 and obesity was defined as a BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
92
1
10

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(114 citation statements)
references
References 24 publications
11
92
1
10
Order By: Relevance
“…Some studies have also reported that number of meals, skipping breakfast, and eating out are associated with obesity. 30,31 However, no relation was found with skipping breakfast or eating out in this study. The present study showed that obese male Japanese workers tended to be in a stressful state, which could be associated with high job demands and low job latitudes.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Some studies have also reported that number of meals, skipping breakfast, and eating out are associated with obesity. 30,31 However, no relation was found with skipping breakfast or eating out in this study. The present study showed that obese male Japanese workers tended to be in a stressful state, which could be associated with high job demands and low job latitudes.…”
Section: Discussioncontrasting
confidence: 68%
“…21,22 This questionnaire is used Obesity and job stress in male Japanese workers N Nishitani and H Sakakibara in some hospitals for obesity treatment in Japan. 23 These 30 questions are classified into the seven areas regarding cognition of constitution (1-3), eating style (4-6), eating rhythm abnormalities (7,8,16,17,30), feeling of satiety (9,10,24,25,28), substitute eating and drinking (11,18,19,(21)(22)(23), meal contents (12)(13)(14)(15)20), and motivation for eating (26,27,29).…”
Section: Study Subjectsmentioning
confidence: 99%
“…One crosssectional study, in the rural west, determined that soda consumption was significantly associated with increased odds of being overweight or obese among both men and women. 21 However, this study defined soda consumption as one or more per week and analyzed weight as a categorical rather than continuous variable, making comparison with our results difficult. Another study determined that consuming one or more sodas per week was associated with increased weight in women.…”
Section: Factors Associated With Soda Consumption In New York City Admentioning
confidence: 89%
“…Based on information from behavioural surveillance and public health practice, respondents were classified as: those who consumed between 1 and 6 sodas/week (moderate consumers) and those who consumed ≥1 soda/d (heavy consumers). These cut-off points were informed by previous benchmarks or questions in population surveys (10,15,16) and by population health research in this subject area (11,(26)(27)(28) .…”
Section: Methodsmentioning
confidence: 99%